Does money change who you are? Quasi-experimental evidence on the effects of wage increases on personality - Adam Ayaita (Deutsches Institut für Wirtschaftsforschung (DIW), 2022)
Using the 2015 introduction of a statutory minimum wage in Germany as a quasi-experiment, I investigate the effects of wage increases on personality. The degree to which each worker's wage is intended to be affected by the reform is used as an instrument for the relative increase in the worker's hourly wage in a two-stage least squares estimation based on nationally representative panel data (N = 1,955 individuals). The results show no significant effects of relative wage increases on personality traits. As the confidence intervals indicate, any substantial effects of wage increases on personality are largely rejected by the results.
Keywords: A12; D31; D63; J31; J38; 330; income; minimum wage; money; personality; quasi-experiment; wage